2017
DOI: 10.1371/journal.pone.0185306
|View full text |Cite|
|
Sign up to set email alerts
|

Self-domestication in Homo sapiens: Insights from comparative genomics

Abstract: This study identifies and analyzes statistically significant overlaps between selective sweep screens in anatomically modern humans and several domesticated species. The results obtained suggest that (paleo-)genomic data can be exploited to complement the fossil record and support the idea of self-domestication in Homo sapiens, a process that likely intensified as our species populated its niche. Our analysis lends support to attempts to capture the “domestication syndrome” in terms of alterations to certain s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
167
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 155 publications
(184 citation statements)
references
References 133 publications
(162 reference statements)
9
167
0
Order By: Relevance
“…That does not make them bad models for the study of social behaviors in general. Many theories about human evolution pose that humans are a self‐domesticated species and that social life creates a hard selective pressure leading to the reduction of reactive aggression . Comparison of humans and other domesticated species (dogs, cats, horses and cattle) has shown an overlap of genes under positive selection that was not present in their wild counterparts .…”
Section: Domesticationmentioning
confidence: 99%
See 2 more Smart Citations
“…That does not make them bad models for the study of social behaviors in general. Many theories about human evolution pose that humans are a self‐domesticated species and that social life creates a hard selective pressure leading to the reduction of reactive aggression . Comparison of humans and other domesticated species (dogs, cats, horses and cattle) has shown an overlap of genes under positive selection that was not present in their wild counterparts .…”
Section: Domesticationmentioning
confidence: 99%
“…Many theories about human evolution pose that humans are a self‐domesticated species and that social life creates a hard selective pressure leading to the reduction of reactive aggression . Comparison of humans and other domesticated species (dogs, cats, horses and cattle) has shown an overlap of genes under positive selection that was not present in their wild counterparts . The concept of “domestication syndrome” has been coined to describe morphological and behavioral changes in domesticated animals and there is some evidence that a common mechanism, related to crest cells function might be, at least partially, a cause of those commonalities .…”
Section: Domesticationmentioning
confidence: 99%
See 1 more Smart Citation
“…We also have tentative accounts of the genetic and epigenetic changes important for the emergence of our language-readiness (Boeckx and Benítez-Burraco, 2014a, 2014b, Benítez-Burraco and Boeckx, 2015, as well as a preliminary hypothesis about how these changes could have been translated to changes in the sort of cognitive abilities that are needed for acquiring and mastering a language (Murphy and Benítez-Burraco 2018a, b). One recent genetic research has shown that candidate genes for domestication in mammals are overrepresented among the genes under positive selection in modern humans compared to extinct hominins (Theofanopoulou et al, 2017). However, no evidence of when these changes were selected is available.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the distance across levels of analysis, from the molecular to the cognitive/behavioral, is not only to be measured in terms of space (Fisher, 2015), but also in terms of time. In addition, the functional consequences of globularization can only be understood in the context of other changes with which globularization stands in a 'feedback loop' relation: (i) the emergence of a cortical vocal learning circuit (Jarvis, 2004;Fitch, 2010), (ii) neurobiological changes leading to increased cooperation (perhaps best understood in terms of self-domestication (Theofanopoulou et al, 2017)), and (iii) contextual factors leading to increased cultural evolution.…”
mentioning
confidence: 99%